Developing Flipbook-Based Physics E-Module to Increase Students’ Learning Outcome and Motivation - Sukma Yuyun; Ahmad Harjono; I Wayan Gunada (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study uses Gall, Gall & Borg model which is a type of research and development (R&D). The purpose of this study is to determine the validity, effectiveness and practicality of flipbook-based e-modules to improve student learning outcomes and motivation. The research was conducted in class XI MAN 2 Mataram with 25 students as respondents. The validity test was carried out by expert validators and practitioner validators with the final product developed being suitable for use in learning. The effectiveness of flipbook-based e-modules for increasing learning outcomes was obtained from the results of N-Gain test analysis which scores a value of 0.68 under the medium category. Meanwhile, increase in learning motivation obtained an index value (%) of 84.12, within the very good category. The practicality of the flipbook-based physics e-module based on the assessment of students obtained an average score of 86.57 in the category of very practical to be used in learning.